Modulation of Free Carbon Structures in Polysiloxane-Derived Ceramics for Anode Materials in Lithium-Ion Batteries - Yiling Quan; Changhao Hu; Peifeng Feng; Yujie Song; Kun Liang; Xigao Jian; Jian Xu (Molecules)
Polymer-derived silicon oxycarbide (SiOC) ceramics have garnered significant attention as novel silicon-based anode materials. However, the low conductivity of SiOC ceramics is a limiting factor, reducing both their rate capability and cycling stability. Therefore, controlling the free carbon content and its degree of graphitization within SiOC is crucial for determining battery performance. In this study, we regulated the free carbon content using divinylbenzene (DVB) and controlled the graphitization of free carbon with the transition metal iron (Fe). Through a simple pyrolysis process, we synthesized SiOC ceramic materials (CF) and investigated the impact of Fe-induced changes in the carbon phase and the amorphous SiOC phase on the comprehensive electrochemical performance. The results demonstrated that increasing the DVB content in the SiOC precursor enhanced the free carbon content, while the addition of Fe promoted the graphitization of free carbon and induced the formation of carbon nanotubes (CNTs). The electrochemical performance results showed that the CF electrode material exhibited a high reversible capacity of approximately 1154.05 mAh g−1 at a low current density of 100 mA g−1 and maintained good rate capability and cycling stability after 1000 cycles at a high current density of 2000 mA g−1.